Evaluation of strength characteristics of mortar and concrete during curing using EMI and surface wave propagation techniques - Nelly Majain (2016)
Concrete is a non-homogenous material with complex microstructure, consisting of water, cement, aggregates and other suitable materials. During concreting of concrete structures, heat will be released due to the hydration process between cement and water. At this stage, curing process is crucial and it needs to be monitored so that the concrete will be able to achieve the desired strength and becomes durable. Due to the complexity of concrete microstructure, the evaluations for concrete curing and strength monitoring are difficult and have moved at a slower pace. However, in recent years the advancements of piezoelectric materials such as Lead Zirconate Titanate (PZT) have attracted interest among researchers to develop new non-destructive evaluation methods to investigate the performance of concrete. The key advantage of using PZT is that it can be placed anywhere even in remote and inaccessible locations as both actuator and sensor to monitor concrete structures. The electromechanical impedance (EMI) and surface wave propagation techniques employing PZT transducer have been developed by researchers as a non-destructive approaches for evaluating concrete. The main objective of this thesis is to evaluate the strength characteristics of mortar and concrete during curing using the EMI and surface wave propagation techniques. In order to achieve this, the research begins with conducting parametric study on free vibration of PZT transducer in the application of EMI technique. The work continues with experimental investigation to study the feasibility of using the EMI and surface wave propagation techniques employing PZT transducer for evaluation of strength characteristics of mortar and concrete during curing. The PZT transducers were attached to the mortar and concrete specimens through surface bonding and embedded methods. The results showed that by using the EMI and surface wave propagation techniques employing the PZT transducer, the duration of concrete setting and curing can be determined. Also, a good correlation between the concrete dynamic modulus of elasticity with compressive strength has been achieved by using the surface wave propagation method. For these reasons, the EMI and surface wave propagation techniques can be a useful tools to ensure the safety and quality of concrete structures during construction and service.